Concise Synthesis of Arylnaphthalene Lignans by Regioselective Intramolecular Anionic Diels–Alder Reactions of 1,7-Diaryl-1,6-diynes - Kudoh, Takayuki; Shishido, Ai; Ikeda, Kyohei; Saito, Seiki; Ishikawa, Teruhiko (Synlett, 2013)
Total synthesis of phyllamycin A and C, justicidin B, and retrojusticidin B from simple arylalkynyl alcohols and (3,4-methylenedioxyphenyl)propynal was accomplished in 4–5 steps by employing an intramolecular anionic Diels–Alder reaction as the key step.
Keywords: lignan; natural products; total synthesis; Diels–Alder reaction; carbanions